The evaluation of objective structure clinical examination (OSCE) implementation within midwifery school - Anisya Selvia; Wiwik Kusumawati; Herlin Fitriani; Mufdlillah Mufdlillah (Journal of Health Technology Assessment in Midwifery, 2019)
Assessment during pre registration in midwifery school is one of the necessary process which need to be concerned as it would strengthen the quality of the graduation. It also could become a tool to evaluate ability and competency of the pre registration midwifery student. There is an evaluation which applied in Indonesian midwifery school as national standard i.e. OSCE in which is considered could fulfil the validity, reliability and feasibility within Indonesian context. This study aimed to evaluate the implementation of OSCE among midwifery school in Yogyakarta. This research was a mixed methods study used sequential explanatory design method i.e. quantitative phase and qualitative phase. Analytic descriptive study was applied in quantitative phase, whilst a case study was applied in  qualitative phase. Quantitative data collection was conducted by using a checklist sheet and analyzed by using descriptive analysis, whilst qualitative data by using in-depth interviews and analyzed by using content analysis. The quantitative result show that the implementation of OSCE among midwifery schools in Yogyakarta has score 68 out of 92. The qualitative analysis showed that OSCE was challenging to be implemented due to technical problems such as broken media of assessment, different phantom model in delivery stages, assessor has been late, assessment rooms were not conducive and there were limited model who skilled as OSCE model. Conclusion: Standardized OSCE implementation has not been carried out properly in midwifery school. Therefore there is a need of national evaluation of the OSCE itself in order to understand the real condition across Indonesian midwifery school.